The Arabidopsis small GTPase AtRAC7/ROP9 is a modulator of auxin and abscisic acid signalling - Nibau, Candida (Oxford University Press, 2013)
Rac-like GTPases or Rho-related GTPases from plants (RAC/ROPs) are important components of hormone signalling pathways in plants. Based on phylogeny, several groups can be distinguished, and the underlying premise is that members of different groups perform distinct functions in the plant. AtRAC7/ROP9 is phylogenetically unique among 11 Arabidopsis RAC/ROPs, and here it was shown that it functions as a modulator of auxin and abscisic acid (ABA) signalling, a dual role not previously assigned to these small GTPases. Plants with reduced levels of AtRAC7/ROP9 had increased sensitivity to auxin and were less sensitive to ABA. On the other hand, overexpressing AtRAC7/ROP9 activated ABA-induced gene expression but repressed auxin-induced gene expression. In addition, both hormones regulated the activity of the AtRAC7/ROP9 promoter, suggesting a feedback mechanism to modulate the signalling output from the AtRAC7/ROP9-controlled molecular switch. High levels of AtRAC7/ROP9 were detected specifically in embryos and lateral roots, underscoring the important role of this protein during embryo development and lateral root formation. These results place AtRAC7/ROP9 as an important signal transducer in recently described pathways that integrate auxin and ABA signalling in the plant.